Moral Ekonomi Perempuan Desa : Studi tentang Resiprositas Budaya dan Disiplin Bisnis Pengrajin Songket di Kecamatan Pemulutan Barat Kabupaten Ogan Ilir - Lasmiana Lasmiana (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2017)
This study discusses economic morals as a result of consideration of cultural reciprocity with business ethics. The study used a qualitative descriptive research step on the economic aspects of the culture of rural songket craftsmen in Pemulutan District, Ogan Ilir Regency. From this research, an overview of the environment in the West Pemulutan Sub-district has a strong social value, so that various activities include activities that increase the prevailing system values. Songket craftsmen, participating in participating, both invited to attend, were also invited to be active in every socio-cultural agenda in the countryside. This activity certainly has an influence on the allocation of time for their business activities as craftsmen both in the production and marketing processes, thus increasing production volume, number of sales, and relations with business relations. In general songket craftsmen have understood, pondered, and let down understanding, but they prioritized togetherness as villagers. The economy of songket craftsmen has stepped on the economy of capital with a pre-capital category, while some are still part of a subsistence economy (enough to meet minimal needs). Income can be increased to a more advanced capital economy with efficiency in transportation aspects and capital control aspects consisting of materials, as well as improving managerial aspects. Activities to maintain togetherness in the countryside, and activities to seek and improve finance are actions that bring benefits so that they can improve conformity with Islamic values. Meanwhile, the economic potential of songket is very large. Furthermore, songket craft activities need to be developed more optimally so that they become part of the road to achieve greater prosperity.